Development of GaN-based ultraviolet and visible light-emitting diodes using hydride vapor-phase epitaxy and molecular epitaxy - Cabalu, Jasper Sicat (Ann Arbor Michigan ProQuest Information and Learning Company, 2006)
Much of the work done on ultraviolet (UV) and visible III-Nitrides-based light emitting diodes (LEDs) involves growth by metal-organic chemical vapor deposition (MOCVD). In this dissertation, the growth, development, and fabrication of III-Nitrides-based UV and visible LEDs with very high photon conversion and extraction efficiencies using hydride vapor-phase epitaxy (HVPE) and radio frequency (rf) plasma-assisted molecular beam epitaxy (PAMBE) is presented. High-power electrically-pumped UV-LEDs based on GaN/AlGaN multiple quantum wells (MQWs) emitting at 340 nm and 350 nm have been fabricated in a flip-chip configuration and evaluated. Under pulsed operation, UV-LEDs emitting at 340 nm have output powers that saturate, due to device heating, at approximately 3 mW. Devices emitting at 350 nm show DC operation output powers as high as 4.5 mW under 200 mA drive current. These results were found to be equivalent with those of UV-LEDs produced by the MOCVD and HVPE methods. The concept of using textured MQWs on UV-LED structures was tested by optical pumping of GaN/AlGaN MQWs grown on textured GaN templates. Results show highly enhanced (>700 times) blue-shifted photoluminescence (PL) at 360 nm compared to similarly produced MQWs on smooth GaN templates whose PL emission is red-shifted. These results are attributed partly to enhancement in light extraction efficiency (LEE) and partly to enhancement in internal quantum efficiency (IQE). The origin of the increase in IQE is partly due to reduction of the quantum-confined Stark effect (QCSE) on QW-planes not perpendicular to the polarization direction and partly due to charge redistribution in the QWs caused by the polarization component parallel to the planes of the QWs. Similar studies have been done for visible LEDs using InGaN/GaN MQWs. Growth of LED structures on textured GaN templates employing textured MQW-active regions resulted in the production of dichromatic (430 nm and 530 nm) phosphorless white LEDs with good electrical characteristics. We attribute this behavior to different incorporation of In in different QW-planes. These studies show that textured MQW-based LEDs not only offers the benefit of enhanced IQE and LEE, but also the benefit of producing efficient white LEDs without the use of phosphor.--Abstract.
Thesis (Ph.D.)--Boston University, 2006.